Roles, perceptions, and context of nursing student clinical facilitation in sub-Saharan Africa: An integrative review - Andrew Mclellan; Shan Mohammed; Edith Tarimo; Augustine Ndaiman; Margaret Phiri; Edith Hillan (Elsevier, 2024)
Background: Effective collaboration between faculty and clinicians, who both act as facilitators in the clinical learning environment, is necessary for the socialization of nursing students to the culture of nursing practice, the expectations of the role, and the realities of the work. Method: A regionally focused integrative review of the literature was conducted to consolidate and consider sub-Sahara African generated research and identify, describe, synthesize, and critically review regional studies examining clinical facilitation from the perspectives of nursing students and clinical facilitators. Results: Five themes emerged from thematic analysis of the literature: the varied roles of clinical facilitation, unconducive learning climates, resources competition, disjointed coordination, conflict facilitation. Conclusion: Clinical facilitation in sub-Sahara Africa (SSA) is characterized by challenges of large student cohorts competing for the attention of limited, uncoordinated, and often unprepared clinical facilitators, with weak links to the university, in a poorly resourced and at times hostile learning environment. The challenges have in some cases been found to undermine the effectiveness of clinical learning and have created difficulties in ensuring and tracking student competency development. The review has unearthed implications for considerations in the future planning of clinical facilitation, the drafting of nursing education policy, and areas for further research.